Phosphorus fractions in the vineyard soil of the Serra Gaúcha of Rio Grande do Sul, Brazil Frações de fósforo no solo de vinhedo na Serra Gaúcha do Rio Grande do Sul - Schmitt D.E.* (2014)
The study aimed to evaluate the accumulation of P fractions in a vineyard soil profile with successive applications of phosphate fertilizers. In January 2010 an area was selected of native forest and a vineyard at age 33 with a history of phosphate fertilizer application, in Bento Gonçalves, Rio Grande do Sul state. Soil samples were collected from 0-5, 5-10 and 10-20 cm layers, prepared and submitted to chemical fractionation of P. The excessive application of phosphate fertilizers during 33 years in the vineyard soil increased the levels of organic and inorganic P until the 20 cm layer in all P fractions. The highest levels of P in the vineyard soil were found mainly in the labile fractions extracted with anion exchange resin and NaHCO3, which indicates high nutrient availability to plants, but also indicates the potential of transfer of solution from soil to surface run-off or percolated through the soil profile, which represents greater potential for contamination of surface and subsurface waters.